Labor geographies: workers and the landscapes of capitalism - Herod, Andrew (New York, 2001)
"Discussions of the geographic transformations wrought by capitalism generally treat corporations as the primary agents of spatial change. We hear of billions of dollars flowing here, factories moving there, venture capitalists opening up new markets, and workers having to "take it or leave it." Yet labor too is increasingly thinking and acting geographically, whether by struggling to impose national contracts; building regional, national, or international links of solidarity; or engaging in debates over local economic development. This book provides a comprehensive introduction to the emerging discipline of labor geography. Combining innovative theoretical analysis with empirical case studies from around the world, Herod examines the spatial contexts and scales in which workers live, organize, and work to address particular economic and political problems. The first book-length text of its kind, this is an indispensable resource for anyone interested in working-class life, workers' organizations, and the contemporary dynamics of capitalism."